Preferences and Perceptions of Workplace Participation: A Cross-Cultural Study - Wu, Sherry Jueyu; Yuhan Mei, Bruce; Cervantez, Jose (Frontiers in Psychology, 2022)
Despite the amount of theorization on the forms and effects of participation, relatively little research directly examines what the concept of workplace participation entails in the minds of employees, and whether employees across cultures think positively when the concept of participation is activated in their mental representation. Three studies (n = 1,138 full-time employees) investigated the perceptions and preferences of full-time employees from the United States and China, cultures that might be expected to differ in their societal participation norm. Using a free association test and text analyses, Study 1 demonstrated that Chinese and American employees differed in their construal of workplace participation, yet both culture groups associated positive valence to the concept of participation. Study 2 showed that employees’ preference for workplace participation is positively related to their perceptions of its outcomes on productivity, job satisfaction, and workplace conflict. Study 3 had employees interact with either a prototypically high or low participation work environment and tested whether clearer cultural contrasts might occur. American employees expressed unambiguous endorsement and predicted positive outcomes of a high participation workplace, whereas Chinese employees expressed slightly higher endorsement to a low participation work environment and associated it with higher productivity. This research provides insights on how workplace participation is construed by employees from different cultures, especially from cultures where democratic participation is not the normative default. Different perspectives on workplace participation across cultures may inform practitioners of the goals and approaches when shaping a more participatory workplace and a more democratic society.